Infectious and Noninfectious Acute Pericarditis in Children: An 11-Year Experience - Nahed Abdel-Haq; Zeinab Moussa; Mohamed Hani Farhat; Leela Chandrasekar; Basim I. Asmar (International Journal of Pediatrics)
Objective. The study was undertaken to determine the etiology, review management, and outcome in children diagnosed with acute pericarditis during 11 years at tertiary pediatric institution. Methods. Retrospective chart review of children diagnosed between 2004 and 2014. Patients with postsurgical pericardial effusions were excluded. Results. Thirty-two children were identified (median age 10yr/11mo). Pericardiocentesis was performed in 24/32 (75%) patients. The most common cause of pericarditis was infection in 11/32 (34%), followed by inflammatory disorders in 9 (28%). Purulent pericarditis occurred in 5 children including 4 due to Staphylococcus aureus: 2 were methicillin resistant (MRSA). All patients with purulent pericarditis had concomitant infection including soft tissue, bone, or lung infection; all had pericardial drain placement and 2 required pericardiotomy and mediastinal exploration. Other infections were due to Histoplasma capsulatum (2), Mycoplasma pneumoniae (2), Influenza A (1), and Enterovirus (1). Pericarditis/pericardial effusion was the initial presentation in 4 children with systemic lupus erythematosus including one who presented with tamponade and in 2 children who were diagnosed with systemic onset juvenile inflammatory arthritis. Tumors were diagnosed in 2 patients. Five children had recurrent pericarditis. Systemic antibiotics were used in 21/32 (66%) and prednisone was used in 11/32 (34%) patients. Conclusion. Infections remain an important cause of pericarditis in children. Purulent pericarditis is most commonly caused by Staphylococcus aureus and is associated with significant morbidity, need of surgical intervention, and prolonged antibiotic therapy. Echocardiography-guided thoracocentesis remains the preferred diagnostic and therapeutic approach. However, pericardiotomy and drainage are needed when appropriate clinical response is not achieved with percutaneous drainage.